Brodalumab for Treatment-Resistant Psoriasis: Case Reports and Safety Update. Issue 3 (July 2020) - Brownstone, Nicholas D.; Reddy, Vidhatha; Thibodeaux, Quinn; Chan, Stephanie; Myers, Bridget; Bhutani, Tina; Koo, John Y. M.
Introduction: Brodalumab is an interleukin-17 receptor blocker that is effective for the treatment of psoriasis. However, due to a Food and Drug Administration black box warning on depression and suicide, many providers are hesitant to use this agent despite its efficacy. Methods: We present the cases of 2 brothers seen at our clinic with treatment-resistant psoriasis who were both successfully treated with brodalumab, despite failing 6 other biologics. We also review the safety profile of brodalumab regarding the currently available evidence on the increased risk of suicidality or depression in patients treated with brodalumab. Results: Both patients achieved completely clear skin and maintained clearance on brodalumab. Discussion: Brodalumab appears to be an effective agent in severe treatment-resistant cases of psoriasis. In addition, a causal relationship between increased risk of suicidality or depression and brodalumab use has not been established.